Prevalence of Metabolic Syndrome among Obese Children and Adolescents - Mohsin, F; Baki, A; Nahar, J; Akhtar, S; Begum, T; Azad, Kishwar; Nahar, Nazmun (BIRDEM Medical Journal, 2012)
Objectives: The Prevalence and magnitude of childhood obesity are increasing dramatically. The study was undertaken to see the prevalence of metabolic syndrome among children and adolescents with obesity, attending the Paediatric Endocrine OPD, BIRDEM. Methods: A cross sectional study was conducted from January 2006 to December 2008 among obese children and adolescents (6-18 years) attending Paediatric endocrine out patient department of BIRDEM. Children with any other endocrine disorder, dysmorphism/syndrome were excluded. Obesity was defined as BMIe95th percentile for age and sex using CDC growth chart. Children underwent two-hour oral glucose tolerance test, anthropometric and blood pressure measurement. Fasting serum insulin and lipid profile were measured. Impaired glucose tolerance (IGT) was defined as fasting plasma glucose (FPG) <7 mmol/L and 2 hr post glucose load e7.8 mmol/L to<11.1 mmol/L. Metabolic syndrome was identified if 3 or more of following criteria were met: BMI > 97th percentile for age and sex, high triglyceride (TGe150 mg/dl), low high-density lipoprotein cholesterol (HDL cholesterol<40mg/dl), Systolic or diastolic blood pressure>95th percentile for age and sex, IGT. Results: A total of 161 children presented with obesity. Male to female ratio was 1.3:1. Mean age was 10.3±2.5 years. Metabolic syndrome was identified in 36.6% subjects (59 out of 161, twenty five male and 34 female). Higher BMI and hip circumference, systolic and diastolic hypertension, high TG, low HDL cholesterol and IGT were significantly associated with metabolic syndrome. Conclusions: The prevalence of metabolic syndrome is high among obese children and adolescents. Factors contributing towards obesity needs to be identified and strategies should be planned for prevention and management of this health problem. DOI: http://dx.doi.org/10.3329/birdem.v1i1.12382 Birdem Med J 2011; 1(1): 21-25